e-Studio : [e]volution or architecture studio in cyber age - 409052 Tseng, Hsien Shin (Skudai : Universiti Teknologi Malaysia, 2004)
Project Paper (Sarjana Muda Senibina) - Universiti Teknologi Malaysia, 2004